Adventures in Yiddishland : postvernacular language & culture - Shandler, Jeffrey (University of California Press, 2006)
Adventures in Yiddishland examines the transformation of Yiddish in the six decades since the Holocaust, tracing its shift from the language of daily life for millions of Jews to what the author terms a postvernacular language of diverse and expanding symbolic value. With a thorough command of modern Yiddish culture as well as its centuries-old history, Jeffrey Shandler investigates the remarkable diversity of contemporary encounters with the language. His study traverses the broad spectrum of people who engage with Yiddish--from Hasidim to avant-garde performers, Jews as well as non-Jews, flu.